Reconsideration of the current models of estimated kidney function‐based drug dose adjustment in older adults: The role of biological age - Radin Alikhani; Manjunath P. Pai (Clinical and Translational Science, 2023)
Abstract Human lifespan has increased from a median of 46.5 years in 1950 to 71.7 years in 2022. As people age, one of the inevitable consequences is a decline in kidney function and glomerular filtration rate (GFR) which can have direct or indirect effects on the pharmacokinetic and pharmacodynamic profiles of many drugs. Numerous equations have been developed to generate estimated GFR (eGFR) using the two principal biomarkers: serum creatinine and serum cystatin C. However, the trajectory of changes with aging is dissimilar in these equations. In addition, there is recognition that chronological age (lifespan) often does not reflect biological age (healthspan) as an essential parameter in kidney function equations. In the past decade, there has been an increasing interest in quantifying biological age and new commercially available assays have entered the marketplace. In this narrative review, we illustrate how dominant equations of eGFR model the fractional change in this parameter very differently across chronological age. In addition, we review various biological age indicators (aging clocks) and challenges to their application in clinical practice. Importantly, by comparing vancomycin's mean clearance as a drug with limited metabolism and unchanged elimination between two age milestones in some recent population pharmacokinetic models, we show how efforts to quantify kidney function in older adults optimally remain under‐explored, particularly those at the upper end of their lifespan. We also propose considering new models that integrate biological age as a new pathway to improve precision drug dosing in older adults.